PENGARUH PROFITABILITAS, LIKUIDITAS, DAN RISIKO BISNIS PADA SRUKTUR MODAL PERUSAHAAN PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA - Mufidah, Mufidah; Ulupui, I Gusti Ketut Agung; Prihatni, Rida (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2018)
ABSTRACT This study was conducted to obtain empirical evidence on the influence of profitability, liquidity, and business risk on capital structure. This research was conducted since June 2017 and used secondary data obtained from annual reports of property and real estate companies in property, real estate and construction of Indonesia Stock Exchange. The sample used in this research is 30 companies for three years, namely 2013-2015. The sample was obtained through purposive sampling technique.The analysis method used is descriptive statistical analysis, analysis of classical assumption test, and multiple linear regression analysis. The result of this research is liquidity has significant negative effect to capital structure, while profitability and business risk have no significant effect to capital structure. Keywords : Profitability, Liquidity, Business Risk, Capital Structure